Optimization and Physical Quality Evaluation of Sacha Inchi (Plukenetia volubilis L.) Seed Oil Emulgel Formulated with Varying Concentrations of Tween 80 and Span 80 Using the Simple Lattice Design (SLD) Method - Shabrina Nindya Hutami; Taufik Turahman; Ilham Kuncahyo; Septiawan Adi Nugroho (Generics: Journal of Research in Pharmacy, 2026)
Sacha inchi (Plukenetia volubilis L.) seed oil is a promising bioactive ingredient for topical applications due to its high content of essential fatty acids and antioxidants; however, its hydrophobic nature limits formulation stability and performance. This study aimed to develop and optimize an emulgel delivery system using a systematic mixture design approach to enhance its physicochemical characteristics. A Simplex Lattice Design (SLD) was applied to evaluate the combined effects of Tween 80 (1-5%) and Span 80 (1-5%) on key responses, including pH, viscosity, and adhesion. Emulgel formulations were prepared using a conventional emulsification method followed by incorporation into a gel base, then evaluated accordingly. Data were analyzed using Design Expert® software and ANOVA. The results showed that all formulations met the acceptable criteria for topical application, with pH (5.40–6.30), viscosity (25.1–61.2 P), and adhesion (1.46–3.5 s). Statistical analysis revealed a significant (p < 0.05) and non-linear interaction between surfactants across all responses, indicating the critical role of compositional balance. The optimized formulation, containing 5% Tween 80 and 1% Span 80, achieved a desirability value of 1.00. Overall, the SLD approach proved effective for optimizing emulgel formulations and enhancing the potential of sacha inchi oil as a stable topical delivery system.